INNOVATIONS IN MEDICAL EDUCATION: TRANSFORMING LEARNING IN THE DIGITAL AGE.: JPUMHS;2024:14:03,1 2.http://doi.org/10.46536/jpumhs/2024/14.03.527 - Anwar Ali jamali (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
Medical education has undergone significant transformations over the last decade through leaps in technological advancements and evolutionary pedagogical philosophies. Healthcare delivery has become increasingly complex; hence, future healthcare professionals must be able to handle such challenges. The most significant development has been the embracing of new digital tools, competency-based curricula, and simulation based learning in medical education, all of which will revolutionize old teaching modes.